ASSESSMENT OF MENTAL SUFFERING AND LEVELS OF ANXIETY AND DEPRESSION IN PARENTS OF CHILDREN ADMITTED TO A PEDIATRIC ICU IN GOIÁS - Souza, Carlos Eduardo Gomes; Souza, Henrique Souza Lemos; Oliveira, Saulo Henrique Dias; Carvalho, Karla Cristina Naves de (CIPEEX, 2025)
The Pediatric Intensive Care Unit is a hospital environment that provides intensive care for children in delicate medical conditions. Thus, for the family, the hospitalization of a child in the PICU is a difficult experience that brings feelings of anxiety, distress, fear, and stress, making them more vulnerable to emotional instability. The objective of this study was to assess mental distress and levels of anxiety and depression in parents of children admitted to the Pediatric Intensive Care Unit. This is an analytical, observational, cross-sectional study conducted from November 2023 to March 2024 with 30 family members of children admitted to the pediatric ICU at Santa Casa de Anápolis-Goiás, Brazil. The Self-Reporting Questionnaire (SRQ-20) was used to assess mental distress, while the Hamilton Anxiety and Depression Scale (HAD) was used to analyze anxiety and depression. In the present study, 66.3% of parents reported mental distress on the SRQ-20. In addition, 46.7% of parents had probable anxiety, and 33.3% had probable depression. Therefore, the study reveals the profound emotional impact of a child’s hospitalization on their parents, making it necessary to seek ways to mitigate parental suffering.